Gutiérrez-Noriega and debate about the consumption of coca leaves (1937 – 1952) - Ayala Pío, Salomón (2018)
This study is an academic historical investigation that analyzes the work of the San Marcos University researcher Carlos Gutiérrez- Noriega in the debates about the health consequences of the coca consumption habit in the peruvian people. The context of the discussions during that period of time are reviewed, as well as, the systematic studies of the research developed by Gutiérrez- Noriega and his associates about the coca consumption in the andean people in Peru and the cocaine effects by experimental observations. The evidence about the coca harmful effects produced by the author is examined in the debates and political decisions about coca consumption in national and international policy.